The Effect of Different Large of Aquarium and Stocking Density on Growth and Survival Rate of Gouramy Larvae (Osphronemus goramy) - Marlin, Rosita; Aryani, Netti; Nuraini, Nuraini (Jurusan Budidaya Perairan, Fakultas Perikanan dan Kelautan, Universitas Riau, 2024)
This research aims to find the best large aquarium and stocking density for the goramy larvae and survival rate of g. This research was carried out in March – Mei 2022 at the Fish Hatchery and Breeding Laboratory, Faculty of Fisheries and Marine, Universitas Riau. This research method used a Completely Randomized Design with two factors and three replications. The first factor is the different large of an aquarium with three treatments each (30x30x30 cm, 40x30x30 cm, and 50x30x30 cm), and the second factor is stocking density of larvae with three treatments each (4 fish L-1, 6 fish L-1, and 8 fish L-1). The treatment in this research namely Lw1Pt4, Lw1Pt6, Lw1Pt8, Lw2Pt4, Lw2Pt6, Lw2Pt8, Lw3Pt4, Lw3Pt6, Lw3Pt8. The result showed that different amounts of aquarium and stocking density had a significant effect (P<0,05). The best result was Lw2Pt4 (Different large aquarium 40x30x30 cm + Stocking Density 4 fish L-1) with absolute weight growth of 29.13 grams, an absolute length growth of 2.40 cm, a specific growth rate of 9.05 %/day and a survival rate of 99.66%. The water quality parameters during research ranged from 26–27oC, pH 6-7, and dissolved oxygen (DO) from 4.5-5.6 ppm